2015
DOI: 10.1016/s0140-6736(15)00163-4
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen saturation targets in infants with bronchiolitis (BIDS): a double-blind, randomised, equivalence trial

Abstract: SummaryBackgroundThe American Academy of Pediatrics recommends a permissive hypoxaemic target for an oxygen saturation of 90% for children with bronchiolitis, which is consistent with the WHO recommendations for targets in children with lower respiratory tract infections. No evidence exists to support this threshold. We aimed to assess whether the 90% or higher target for management of oxygen supplementation was equivalent to a normoxic 94% or higher target for infants admitted to hospital with viral bronchiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
123
1
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(141 citation statements)
references
References 23 publications
6
123
1
6
Order By: Relevance
“…This is a highly relevant issue for acute respiratory tract infection programs where pulse oximetry has become an essential tool for making clinical decisions. 10,11 The median PB was 7.2% and was significantly higher than that published at sea level, which was reported to be 1.1% among young infants, 12 and was also higher than that reported at 2560 MASL, which was 4.9%. 6 The CSAI was higher than that observed at 2560 MASL 6 and much higher than that published at sea level.…”
Section: Discussioncontrasting
confidence: 54%
“…This is a highly relevant issue for acute respiratory tract infection programs where pulse oximetry has become an essential tool for making clinical decisions. 10,11 The median PB was 7.2% and was significantly higher than that published at sea level, which was reported to be 1.1% among young infants, 12 and was also higher than that reported at 2560 MASL, which was 4.9%. 6 The CSAI was higher than that observed at 2560 MASL 6 and much higher than that published at sea level.…”
Section: Discussioncontrasting
confidence: 54%
“…16,28 Our decision to use <90% as a threshold is based on the latest American Academy of Pediatrics recommendation 1 and on recent evidence revealing comparable outcomes in patients discharged with a saturation threshold of 90% vs 94%. 58 Interestingly, duration of symptoms was not associated with escalated care in this study. Although previous evidence for this association has yielded disparate results, 16,19,20,23 a large multisite study revealed that symptom duration <1 day predicts the need for ICU care in bronchiolitis.…”
Section: Figurementioning
confidence: 46%
“…94 Other information that will be important to include in the pre-trial information includes data to support the switch point in both standard care and the experimental intervention, details of how a child would be monitored to ensure infection was being dealt with, trajectory of care in case of failure to recover in the shorter treatment arm, and data to demonstrate safety of the shorter arm and regarding the equivalence/equipoise about treatment in both arms.…”
Section: Logistics Of a Clinical Trial Including Criteria For Oral Swmentioning
confidence: 99%